(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2025)
Type 2 Diabetes Mellitus is a metabolic disorder characterized by elevated blood glucose levels. There is significant interest in developing alternative treatments for type 2 diabetes mellitus, particularly through the identification of phytochemicals capable of inhibiting glucose absorption. The inhibition of intestinal alpha-glucosidase can delay the digestion of starch and sucrose. Jengkol fruit peel decoction is traditionally believed to regulate blood glucose levels. This experimental study aimed to provide in vitro evidence for the potential inhibition of α-glucosidase, achieving a 50% reduction in α-glucosidase activity. The ethanol extract of jengkol fruit peel was obtained through the maceration of plant powder using 96% ethanol. The inhibition assay involved reactions with extracts compared to Acarbose. The concentration of extract used for the kinetics test was that which could inhibit the enzyme by 50%. Absorbance was measured using an ELISA reader. IC50 values were derived from the linear regression of absorbance against extract concentration. The results indicated that jengkol fruit peel extract can inhibit α-glucosidase activity, with an IC50 of 94.038 µg/ml, whereas the IC50 of the standard (glukobay) is 0.757 µg/ml. This study suggests that the extract of Archidendron pauciflorum holds promise as an antidiabetic agent, particularly for the treatment of type II diabetes mellitus.